Capacity building on improved forages in partnership with AICCRA, Lewa Wildlife Conservancy and Chuka University - Nderi, Alex Nduah; Ogutu, Elizabeth; Gichunge Kathure, Karen; Nzuki, Esther Ndumi; Muthomi, Fredrick Kathurima (2025)
A comprehensive capacity-building program on improved forages was implemented in Meru, Isiolo, and Tharaka Nithi counties, Kenya, through a strategic partnership between theAICCRA project, Lewa Wildlife Conservancy, and Chuka University. The initiative addressed critical constraints to livestock productivity caused by seasonal forage scarcity, a challenge increasingly aggravated by climate variability. The program promoted the adoption of climate-resilient forage varieties such as Brachiaria hybrids (Mulato II, Camello, Cayman, Cobra) and Panicum siambaza selected for their drought tolerance, high biomass yield, and superior nutritional quality. This partnership-driven model established a strong foundation for scaling climate-smart forage solutions. It equips smallholder farmers with practical tools and knowledge to enhance livestock productivity, improve feed security, and strengthen resilience to climate change.